Feasibility Study for the MALDI‐MSI Analysis of Thyroid Fine Needle Aspiration Biopsies: Evaluating the Morphological and Proteomic Stability Over Time. Issue 1 (20th November 2018) - Piga, Isabella; Capitoli, Giulia; Tettamanti, Silvia; Denti, Vanna; Smith, Andrew; Chinello, Clizia; Stella, Martina; Leni, Davide; Garancini, Mattia; Galimberti, Stefania; Magni, Fulvio; Pagni, Fabio
Abstract : Purpose: MALDI–MS imaging (MALDI–MSI) is an emerging technology that enables the spatial distribution of biomolecules within tissue to be combined with the traditional morphological information familiar to clinicians. Thus, for diagnostic or prognostic purposes, along with predicting response to therapeutic treatment, it is important to properly collect and handle biological specimens in order to avoid degradation or the formation of artifacts in the morphological structure and proteomic profile. Experimental design: In this work, the morphological and proteomic stability of thyroid fine needle aspiration biopsies in PreservCyt (up to 14 days) and CytoLyt (up to 7 days) solutions at 4 °C has been verified, by MALDI–MSI analysis. Moreover, a new measure has been introduced in order to assess the similarity of the obtained MALDI–MSI spectra, by equally taking into account the number of signals (fit and retrofit), and their intensities (Spearman's correlation and spectra overlap). Results: Results show no degradation of the cellular morphology and a good stability of the samples up to 14 days in PreservCyt solution. Conclusions and clinical relevance: Moreover, this protocol can be easily implemented in pathological units, allowing simple sample collection and shipment to be used not only for the proteomic MALDI–MSI analysis of thyroid FNABs but also for other biological liquid based specimens.